Exercise-Induced Regulation of Redox Status in Cardiovascular Diseases: The Role of Exercise Training and Detraining - Tofas, Tryfonas (Antioxidants (Basel), 2019)
Although low levels of reactive oxygen species (ROS) are beneficial for the organism ensuring normal cell and vascular function, the overproduction of ROS and increased oxidative stress levels play a significant role in the onset and progression of cardiovascular diseases (CVDs). This paper aims at providing a thorough review of the available literature investigating the effects of acute and chronic exercise training and detraining on redox regulation, in the context of CVDs. An acute bout of either cardiovascular or resistance exercise training induces a transient oxidative stress and inflammatory response accompanied by reduced antioxidant capacity and enhanced oxidative damage. There is evidence showing that these responses to exercise are proportional to exercise intensity and inversely related to an individual’s physical conditioning status. However, when chronically performed, both types of exercise amplify the antioxidant defense mechanism, reduce oxidative stress and preserve redox status. On the other hand, detraining results in maladaptations within a time-frame that depends on the exercise training intensity and mode, as high-intensity training is superior to low-intensity and resistance training is superior to cardiovascular training in preserving exercise-induced adaptations during detraining periods. Collectively, these findings suggest that exercise training, either cardiovascular or resistance or even a combination of them, is a promising, safe and efficient tool in the prevention and treatment of CVDs.